Correlation between Organizational Roles, OBC, and Organizational Commitment toward Employees of the Limited Liability Company of State Electricity Company of APJ Jember - Abd. Syakur; Woro Utari; Chamariyah Chamariyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aimed to determine the influence of organization commitment to Organizational Citizenship Behavior (OCB). The sample at the Limited Liability Company of APJ Jember area, it is state-owned company that operates in the electricity sector with total of 82 employees. Researchers collected data by using questionnaires, documentation study, interviews and surveys. Testing of validity, reliability, normality, multicolinearity, heteroscedasticity, and hypotheses was carried out using IBM SPSS 17.00. The results showed that there was influence from the organizational culture; Organizational Citizenship Behavior simultaneously improved the workforce performance in the scope PT. PLN (Persero) of APJ Jember. This result either culture, OCB and the organization had positive and meaningful influence in improving employee performance. Organizational commitment had very significant / dominant influence and was able to improve employee performance more optimally than organizational culture and organizational citizenship behavior.